2016
DOI: 10.7763/ijesd.2016.v7.787
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetry Determination from High Resolution Satellite Imagery Using Ensemble Learning Algorithms in Shallow Lakes: Case Study El-Burullus Lake

Abstract: Abstract-Determination of bathymetric information is key element for near off shore activities and hydrological studies such as coastal engineering applications, sedimentary processes and hydrographic surveying. Remotely sensed imagery has provided a wide coverage, low cost and time-effective solution for bathymetric measurements. In this paper a methodology is introduced using Ensemble Learning (EL) fitting algorithm of Least Squares Boosting (LSB) for bathymetric maps calculation in shallow lakes from high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Experiments there showed that the localized model reduced the bathymetry estimation error by 60% from an RMSE of 1.23m to 0.48m. In (Mohamed et al, 2016) a methodology is introduced using an Ensemble Learning (EL) fitting algorithm of Least Squares Boosting (LSB) for bathymetric maps calculation in shallow lakes from high resolution satellite images and water depth measurement samples using Echo-sounder. The retrieved bathymetric information from the three methods was evaluated using Echo Sounder data.…”
Section: Bathymetry Determination Using Machine Learningmentioning
confidence: 99%
“…Experiments there showed that the localized model reduced the bathymetry estimation error by 60% from an RMSE of 1.23m to 0.48m. In (Mohamed et al, 2016) a methodology is introduced using an Ensemble Learning (EL) fitting algorithm of Least Squares Boosting (LSB) for bathymetric maps calculation in shallow lakes from high resolution satellite images and water depth measurement samples using Echo-sounder. The retrieved bathymetric information from the three methods was evaluated using Echo Sounder data.…”
Section: Bathymetry Determination Using Machine Learningmentioning
confidence: 99%
“…In this section, the radiative transfer model of the water column is described in brief followed by methods to extend SBR (or NDR) to RDLC for the LCC estimation in multispectral satellite images. The main idea comes from the following two aspects: (1) based on previous studies on hyperspectral data, LCCs should correlate linearly to a particular SBR (or NDR); (2) according to the principle of band combination bathymetric methods [39][40][41][42][43], there is an approximate linear dependence between the water depth and the combination of different bands.…”
Section: Methodsmentioning
confidence: 99%
“…Most of those methods are based on the relationship between the reflectance and the depth. Some of them exploit an SVM system to predict the correct depth [45,46]; experiments therein showed that the localized model reduced the bathymetry estimation error by 60% from a Root Mean Square Error (RMSE) of 1.23 m to 0.48 m. In [47] a methodology is introduced using an ensemble learning (EL) fitting algorithm of least squares boosting (LSB) for bathymetric map calculations in shallow lakes from high resolution satellite images and water depth measurement samples using an echo sounder. The bathymetric information retrieved from the three methods [45][46][47] was evaluated using echo sounder data.…”
Section: Image-based Bathymetry Estimation Using Machine Learning Andmentioning
confidence: 99%
“…Some of them exploit an SVM system to predict the correct depth [45,46]; experiments therein showed that the localized model reduced the bathymetry estimation error by 60% from a Root Mean Square Error (RMSE) of 1.23 m to 0.48 m. In [47] a methodology is introduced using an ensemble learning (EL) fitting algorithm of least squares boosting (LSB) for bathymetric map calculations in shallow lakes from high resolution satellite images and water depth measurement samples using an echo sounder. The bathymetric information retrieved from the three methods [45][46][47] was evaluated using echo sounder data. The LSB fitting ensemble resulted in an RMSE of 0.15 m where the Principal Component Analysis (PCA) and Generalized Linear Model (GLM) yielded RMSEs of 0.19 m and 0.18 m respectively, over shallow water depths less than 2 m. In [48], among other pre-processing steps, authors implemented and compared four different empirical SDB (satellite-derived bathymetry) approaches to derive bathymetry from pre-processed Google Earth Engine Sentinel-2 composites.…”
Section: Image-based Bathymetry Estimation Using Machine Learning Andmentioning
confidence: 99%